Fetomaternal outcome of pregnancy complicated by first and second trimester vaginal bleeding - Jakhetiya, Bhamini; Khan, Ruhina; Gupta, Arun; Chundawat, Rama; Singh, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To determine the effects of vaginal bleeding occurring in first and second trimester on maternal and fetal outcome. Methods: The present prospective observational study was conducted at department of obstetrics and gynecology, Geetanjali medical college and hospital, Udaipur and 90 Patients with first and second trimester pregnancy (till 24 weeks of gestation) presented with the complaint of vaginal bleeding at antenatal clinic or emergency were included in this study. Results: In our study the result showed that bleeding in early pregnancy is associated with high rate of abortion (32.22%) in which first trimester abortion constitute 44.83% while second trimester abortion constitute around 55.17%. Outcome observed in women having bleeding with SCH 58.4% had caesarean delivery followed by 25% had vaginal delivery, 16.7% had preeclampsia, 8.3% had PPROM and 5.6% had APH. Similarly, in women having bleeding without SCH 64% had caesarean delivery followed by 36% had vaginal delivery, 12% had preeclampsia, PPROM and APH in 8% each and also women having bleeding with SCH, 37.1% had low birth babies, 22.8% had NICU admission and 8.6% had birth asphyxia. Similarly, in women having bleeding without SCH, 16% had low birth babies, 16% had NICU admission and 8% had birth asphyxia. Conclusions: First and second trimester vaginal bleeding is an independent risk factor for an adverse obstetric outcome and this risk factor should be taken into consideration when deciding upon antenatal surveillance and management.